2019
DOI: 10.1111/ina.12546
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods for converting Dylos particle number concentrations to PM2.5 mass concentrations

Abstract: The aim of this study was to (a) develop a method for converting particle number concentrations (PNC) obtained by Dylos to PM2.5 mass concentrations, (b) compare this conversion with similar methods available in the literature, and (c) compare Dylos PM2.5 obtained using all available conversion methods with gravimetric samples. Data were collected in multiple residences in three European countries using the Dylos and an Aerodynamic Particle Sizer (APS, TSI) in the Netherlands or an optical particle counter (OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…for two channels of > 0.5 µm (small) and > 2.5 µm (large) sampled at intervals of one minute. A particle count with size range 0.5 -2.5 µm was calculated by subtracting the large channel from the small channel as this has been found to correlate with PM2.5 mass concentrations [63][64][65]. An equivalent mass concentration was computed using the PM2.5 conversion factor from Semple et al [63] because that investigation also considered homes with smoking.…”
Section: Measurementsmentioning
confidence: 99%
“…for two channels of > 0.5 µm (small) and > 2.5 µm (large) sampled at intervals of one minute. A particle count with size range 0.5 -2.5 µm was calculated by subtracting the large channel from the small channel as this has been found to correlate with PM2.5 mass concentrations [63][64][65]. An equivalent mass concentration was computed using the PM2.5 conversion factor from Semple et al [63] because that investigation also considered homes with smoking.…”
Section: Measurementsmentioning
confidence: 99%
“…Therefore, it may be necessary to test this new device before it is applied in a high spatial-temporal resolution exposure assessment study. As a proper calibration protocol providing a correction factor can have a dramatic impact on precision, accuracy and bias of a real-time monitor, researchers evaluated the OPC or photometers for use in the laboratory, outdoors or in the home in other countries [3,9,[13][14][15][16]. A recent article reported that "one size fits all" approach to obtain PM 2.5 mass concentrations by OPC result in relatively high uncertainty in complex exposure situations.…”
Section: Introductionmentioning
confidence: 99%
“…A recent article reported that "one size fits all" approach to obtain PM 2.5 mass concentrations by OPC result in relatively high uncertainty in complex exposure situations. Although OPC Therefore, corresponding conversion curve approach may be most valuable when a relatively high contrast is expected in exposure levels for example, daytime home with indoor combustion sources, BBQ or secondhand smoke versus night time or day time outside with heavy traffic volume versus night time [16]. To our knowledge, no one has rigorously evaluated the performance of IRMs, operated with OPC or photometer, in Korea with comparison of the U.S. Federal Equivalent Method (US FEM) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Further information regarding the AFM-MCS sen sor was described in [27]. Furthermore, the DC1100-PRO (Figure 6b) is an optical-based particle counter that is commercially available to measure particle number concentration (PNC) in the two size bins (>0.5 and >2.5 μm) [28]. The DC1100-PRO is a compact particle counter with dimensions of (18 cm × 12 cm × 8 cm) and a weight of 1.1 kg.…”
Section: Real-time Cigarette Smoke Detectionmentioning
confidence: 99%